Partisipasi Perempuan Dalam Eksistensi Home Industry (Studi Kasus: Rumah Produksi Jamur di Desa Kamasan Kabupaten Serang Banten) - Yuliani, Nurul Hayat, Stevany Afrizal (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
Women's active involvement in mushroom farming, particularly in Kamasan Village, improves individual skills and family economic resilience. The purpose of this study was to analyze women's participation in the existence of mushroom farming in Kamasan Village, Serang Regency, Banten, and its impact on the sustainability of the mushroom farming. The research method used was descriptive qualitative, with data collection techniques including in-depth interviews, observation, and documentation. This study utilized Naomi Wolf's theory of value equality in mushroom farming. The results indicate that women in Kamasan Village mushroom farming demonstrate a high level of independence, the ability to make assertive decisions, and are given equal opportunities to participate in work and face business challenges. Active participation in mushroom farming not only increases family income but also provides women with a sense of self-confidence, broadens access to public decision-making, and creates a place for other women to thrive. This study concludes that women's participation plays a key role in creating social change and sustainable village community well-being